Guiding Principles for the Conduct of Observational Critical Care Research for Coronavirus Disease 2019 Pandemics and Beyond: The Society of Critical Care Medicine Discovery Viral Infection and Respiratory Illness Universal Study Registry. Issue 11 (November 2020) - Walkey, Allan J.; Sheldrick, R. Christopher; Kashyap, Rahul; Kumar, Vishakha K.; Boman, Karen; Bolesta, Scott; Zampieri, Fernando G.; Bansal, Vikas; Harhay, Michael O.; Gajic, Ognjen
Abstract : Objectives: Use of observational data to inform the response and care of patients during a pandemic faces unique challenges. Design: The Society of Critical Care Medicine Discovery Viral Infection and Respiratory Illness Universal Study COVID 2019 Registry Core data and research methodology team convened over virtual meetings throughout March to June 2020 to determine best practice goals for development of a pandemic disease registry to support rapid data collection and analysis. Setting: International, multi-center registry of hospitalized patients. Patients: None. Interventions: None. Measurements and Main Results: Large-scale observational data collection requires: 1) quality assurance and harmonization across many sites; 2) a transparent process for selecting from among many potential research questions; 3) the use of best practices in design of descriptive, predictive, and inferential studies; (4) innovative approaches to characterize random error in the setting of constantly updated data; (5) rapid peer-review and reporting; and (6) transitions from a focus on discovery to implementation. Herein, we describe the guiding principles to best practices and suggestions for innovations to study design and reporting within the coronavirus disease 2019 Viral Infection and Respiratory Illness Universal Study pandemic registry. Conclusions: Society of Critical Care Medicine Discovery Viral Infection and Respiratory Illness Universal Study coronavirus disease 2019 registry sought to develop and implement prespecified best practices combined with grassroots efforts from clinical sites worldwide in order to develop clinically useful knowledge in response to a pandemic.